2018
DOI: 10.1186/s13584-018-0228-x
|View full text |Cite
|
Sign up to set email alerts
|

The tip of the iceberg: postpartum suicidality in Israel

Abstract: BackgroundPostpartum suicidality, a result of extreme distress or depression, is a tragedy for the woman, infant, and family. Screening for postpartum depression (PPD) is mandatory in Israel, including a question on suicidal ideation. This study presents and analyzes data regarding rates, trends and characteristics of postpartum women who considered, attempted, or completed suicide, to help direct services aimed at preventing these occurrences.MethodsSuicidal ideation data based on PPD screening was drawn from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…There is a global consensus that postpartum depressive disorders exert negative short-and long-term effects on the establishment of motherhood, child development, and family wellbeing [30][31][32][33] and may lead to tragic consequences. For instance, PPD has been found to be a putative cause of disastrous behavioural tendencies, such as suicidal intent [34]. A substantial body of research has reported possible risk factors, e.g., socio-demographic factors, obstetric factors, the course of pregnancy and social support, for the development of postpartum depressive disorders [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…There is a global consensus that postpartum depressive disorders exert negative short-and long-term effects on the establishment of motherhood, child development, and family wellbeing [30][31][32][33] and may lead to tragic consequences. For instance, PPD has been found to be a putative cause of disastrous behavioural tendencies, such as suicidal intent [34]. A substantial body of research has reported possible risk factors, e.g., socio-demographic factors, obstetric factors, the course of pregnancy and social support, for the development of postpartum depressive disorders [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Global perinatal suicide rates range between 1.27 and 3.7 per 100,000 live births [ 22 ]. Israel reports a lower rate of 0.43 per 100,000 live births, or 3.6% of postpartum mortality [ 24 ], reasons for this being religion as a protective factor, or under-reporting of suicide due to mental health stigma. Trost et al [ 4 •] in reviewing pregnancy-related mental health deaths (including suicides and accidental overdoses) in 14 states, found that, 11% of pregnancy-related deaths were due to mental health conditions, and 63% of pregnancy-related mental health deaths were by suicide.…”
Section: Prevalence Of Perinatal Suicide and Perinatal Suicidalitymentioning
confidence: 99%
“…Average infant birthweight was 96.5 g lower for participants with SI compared to those without, and 94.2 g lower after adjusting for confounders. After adjusting for confounders, women with SI had 3.73 × increased odds of small for gestational age infants Glasser et al [ 24 ] The tip of the iceberg: postpartum suicidality in Israel Review/meta-analysis Published and unpublished literature on SI in Israel, and analysis of data on death within a year of childbirth N/A EPDS for SI, Analysis of 193 deaths within a year of childbirth for SA SI and SA Of the 20,259 suicide attempts recorded in EDs of general hospitals in Israel, 565 (2.8%) were by women in the postpartum period. The suicide attempt rate for non-postpartum women was 3 - 5 × that of postpartum women.…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum depression(PPD) is the most common mental disorder for women following childbirth, which can deleteriously affect maternal behaviors and impair the cognitive, behavioral, emotional development of children. [ 1 ] Epidemiological studies have found that women with PPD were at high risk for suicidality, [ 2 ] and almost 1/3 women still reported depressive symptoms even 4 years after childbirth. [ 3 ] Besides, the global pooled incidence of PPD is estimated to be 17.7%, which is up to 38% in Chile.…”
Section: Introductionmentioning
confidence: 99%